Clinical and biomarker assessment of demyelinating events suggesting multiple sclerosis. (1st April 2013) - Gajofatto, A.; Bongianni, M.; Zanusso, G.; Bianchi, M. R.; Turatti, M.; Benedetti, M. D.; Monaco, S.
<x xml:space="preserve">Abstract</x> Background Initial demyelinating event (IDE) diagnosis and prognosis are not straightforward. Objective To identify potential diagnostic markers and outcome predictors of IDEs suggestive of multiple sclerosis (MS), that is, clinically isolated syndromes (CISs). Methods Clinically isolated syndrome cases (i.e., subjects with an IDE compatible with MS onset and no alternative explanation) with at least 1.5 years' follow‐up were retrospectively identified. All cases underwent clinical, neurophysiological, MRI, and cerebrospinal fluid (CSF) assessment, including exploratory tau, 14‐3‐3, and cystatin C testing. CIS recovery, conversion to MS, and long‐term neurological disability were used as outcome measures. Patients with neuromyelitis optica spectrum disorders, idiopathic acute transverse myelitis (IATM), Creutzfeldt–Jacob disease, and non‐inflammatory/non‐neurodegenerative disorders served as controls for CSF analysis. Results Forty‐six CIS cases were included. Severe presentation was associated with incomplete recovery, while presence of at least 3 periventricular lesions on baseline MRI correlated with MS conversion. Initial pyramidal tract involvement, incomplete CIS recovery, and number of relapses predicted neurological disability. CSF tau, 14‐3‐3, and cystatin C did not correlate with any outcome measure. CIS cases had significantly lower tau and cystatin C levels compared to IATM. Conclusions An extensive diagnostic evaluation of patients with an IDE is worthwhile to make prognostic predictions. More robust molecular biomarkers are needed.